Processing of Phonological Variation in Children With Hearing Loss: Compensation for English Place Assimilation in Connected Speech - Skoruppa, Katrin; Rosen, Stuart (My University, 2014)
Purpose In this study, the authors explored phonological processing in connected speech in children with hearing loss. Specifically, the authors investigated these children's sensitivity to English place assimilation, by which alveolar consonants like t and n can adapt to following sounds (e.g., the word ten can be realized as tem in the phrase ten pounds).
Method Twenty-seven 4- to 8-year-old children with moderate to profound hearing impairments, using hearing aids (n = 10) or cochlear implants (n = 17), and 19 children with normal hearing participated. They were asked to choose between pictures of familiar (e.g., pen) and unfamiliar objects (e.g., astrolabe) after hearing t- and n-final words in sentences. Standard pronunciations (Can you find the pen dear?) and assimilated forms in correct (… pem please?) and incorrect contexts (… pem dear?) were presented.
Results As expected, the children with normal hearing chose the familiar object more often for standard forms and correct assimilations than for incorrect assimilations. Thus, they are sensitive to word-final place changes and compensate for assimilation. However, the children with hearing impairment demonstrated reduced sensitivity to word-final place changes, and no compensation for assimilation. Restricted analyses revealed that children with hearing aids who showed good perceptual skills compensated for assimilation in plosives only.